Energy Management in Micro Hydro Power Plant Using Battery Bank - Ghimire, Pallavi; Poudel, Samip; Nepal, Sushma; Pandey, Pratyus; Tamrakar, Indraman; Dhamala, Bhuban (KEC Journal of Science and Engineering, 2023)
Micro Hydro Power (MHP) plants are very much successful for village electrification in Nepal with compared to many other countries in the world. Electrification in rural areas by grid extension seems economically not feasible because of high cost of transmission line and higher power loss in the transmission line. In MHP, the generator is driven by un- regulated water turbine with constant mechanical power output and the speed of the generator is controlled by using ELC. At varying consumer’s load condition, the dump load in ELC consumes excess of power generated by the generator so that total load on the generator at any instant is constant and equal to its full rating resulting in constant speed. In this paper, a new control logic is presented to utilize the wasted energy in the dump load during light load period to charge the battery and utilize it during peak load period. Simulation model of the proposed scheme is developed to study the technical feasibility of the proposed scheme.